Differential Dopaminergic Modulation of Neostriatal Synaptic Connections of Striatopallidal Axon Collaterals - Tecuapetla, Fatuel (Society for Neuroscience, 2009)
Recent studies have demonstrated that GABAergic synaptic transmission among neostriatal spiny projection neurons (SPNs) is strongly modulated by dopamine with individual connections exhibiting either D(1) receptor (D(1)R)-mediated facilitation or D(2) receptor (D(2)R)-mediated inhibition and, at least in some preparations, a subset of connections exhibiting both of these effects. In light of the cell type-specific expression of D(1a)R in striatonigral and D(2)R in striatopallidal neurons and the differential expression of the other D(1) and D(2) family dopamine receptors, we hypothesize that the nature of the dopaminergic modulation is specific to the types of SPNs that participate in the connection. Here the biophysical properties and dopaminergic modulation of intrastriatal connections formed by striatopallidal neurons were examined. Contrary to previous expectation, synapses formed by striatopallidal neurons were biophysically and pharmacologically heterogeneous. Two distinct types of axon collateral connections could be distinguished among striatopallidal neurons. The more common, small-amplitude connections (80%) exhibited mean IPSC amplitudes several times smaller than their less frequent large-amplitude counterparts, principally because of a smaller number of release sites involved. The two types of connections were also differentially regulated by dopamine. Small-amplitude connections exhibited strong and exclusively D(2)R-mediated presynaptic inhibition, whereas large-amplitude connections were unresponsive to dopamine. Synaptic connections from striatopallidal to striatonigral neurons exhibited exclusively D(2)R-mediated presynaptic inhibition that was similar to the regulation of small-amplitude connections between pairs of striatopallidal cells. Together, these findings demonstrate a previously unrecognized complexity in the organization and dopaminergic control of synaptic communication among SPNs.